EFEKTIVITAS MEDIA PUZZLE DALAM MENINGKATKAN KEMAMPUAN LOGIKA MATEMATIKA ANAK USIA DINI - Siti Hadjah, Nandang Faturohman, Subhan (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
The study aims to understand the effectiveness of media puzzles in improving  mathematical skills among children in group A at BKB Kemas Daarul Rohman.  The research used a sample size of 12 students and used observation, observation,  and documentation techniques. The results showed that the use of media puzzles  consistently improved students' mathematical skills. The data before the use of  media puzzles showed a significant increase in students' performance, with 7 out  of 12 students in group BB at 58.3%, 1 child in group MB, 2 children in group  BSH, and 2 children in group BBS. However, the use of media puzzles did notsignificantly improve students' performance in group B, with 10 out of 12 students  at 83.3% performing well in this group. Only 8.3% of students in group B and 8.3%  in group B were still in group B.